Hak Asuh Anak Akibat Perceraian di Desa Karangjati Kecamatan Sampang Kabupaten Cilacap - Eti Mul Erowati; Elisabeth Pudyastiwi; Doni Adi Supriyo (Universitas Wijayakusuma Purwokerto, 2026)
The purpose of this Community Service is to assist the government in socializing the law and increasing public knowledge of the law, especially about child custody due to divorce in Karangjati Village, Cilacap District. In carrying out this Community Service activity which raises the topic